Reorganization of the North Atlantic Oscillation during early Holocene deglaciation - Wassenburg, Jasper; Dietrich, Stephan; Fietzke, Jan; Fohlmeister, Jens; Jochum, Klaus P.; Scholz, Denis; Richter, Detlev K.; Sabaoui, Abdellah; Spötl, Christoph; Lohmann, Gerrit; Andreae, Meinrat O.; Immenhauser, Adrian (Nature geoscience, 2016)
Laurentide ice-sheet retreat continued into the mid-Holocene. Speleothem-based precipitation records suggest the cessation of melt led to the establishment of the present precipitation patterns associated with the North Atlantic Oscillation.
Gesehen am 10.06.2020